Challenging Problems Of Preparing Children For Preschool In Preschool Institutions - Ranokhon Ismoilova; Sardorbek Kosimjon Ugli, Gulomjonov (Procedia of Social Sciences and Humanities, 2022)
This article analyzes important aspects of preparing a child for school. Features such as independence, organization and discipline in the personal behavior of a child of adult preschool age are important in the implementation of moral and voluntary preparation for school. It is the ability to follow the rules of behavior that are inherent in independence, to use the right routines in the new environment, and to be willing to help.